Corporate environmental strategy: a must in the new millennium. (18th July 2007) - Bresciani, Stefano; Oliveira, Nuno
For a long time, companies have been unaware of or unconcerned with their activities' consequences to the environment. In the 1990s, however, this narrow-minded attitude seemed to begin changing, as some signs increasingly appeared: overcompliance with regulation standards, voluntary environmental expenditures and agreements with regulators, the appearance of 'green' products, corporate statements on the environment and implementation of environmental management systems, among others. If companies are now taking the environment into account, they probably have an economic pull for doing so. The interaction process with regulators, stakeholders' pressure, corporate reputation enhancement, creation and taking advantage of competitive opportunities, and the view of corporate environmentalism as a strategic issue are the reasons examined here in order to evaluate the potential benefits for environmental integration in companies' management orientation. This article tries to present corporate environmental strategic management as an essential management function because of its ability to minimise costs and risks and enhance (or ensure) companies' value.